Evolving clinical applications of contrast-enhanced ultrasound (CEUS) in the abdominal aorta - Rafailidis, Vasileios; Partovi, Sasan; Dikkes, Alexander; Nakamoto, Dean A.; Azar, Nami; Staub, Daniel (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2017)
Ultrasound (US) represents the initial modality in the workup of abdominal aortic pathology based on the plethora of advantages including widespread availability, low cost, safety profile and repeatability. However, US has inherent limitations including limited spatial information of pathologic processes to neighboring structures, lower sensitivity to slow blood flow and aortic luminal irregularities. For evaluation of aortic pathology angiography has long been considered the gold standard. Non-invasive cross-sectional imaging techniques like computed tomography angiography (CTA) and magnetic resonance angiography (MRA) have gradually replaced interventional angiography for the evaluation of aorta, currently being regarded as the diagnostic imaging modalities of choice for diagnosis of virtually every aortic disease. Interventional angiography is currently primarily performed for treatment purposes of aortic pathology. The introduction of microbubbles as ultrasonographic contrast agents has rendered contrast-enhanced ultrasound (CEUS) an evolving valuable complementary technique with markedly increased diagnostic accuracy for certain aortic applications. CEUS is characterized by the potential to be performed in patients with impaired renal function. Due to its superior spatial and temporal resolution, ability for prolonged scanning and dynamic and real-time imaging, it provides clinically significant additional information compared to the standard Duplex US. The purpose of this paper is to discuss the currently available literature regarding abdominal aortic applications of CEUS, briefly elaborate on CEUS technique and safety and present cases in order to illustrate the added value in aortic pathologies. Conditions discussed include abdominal aortic aneurysm (AAA), aneurysm rupture, aneurysm surveillance after endovascular repair, dissection and aortitis.